Risk assessment of UST Miguel de Bena Vides library - Cabbuag, Jennylyn G.; Pascua, Sonia M.; Olgado, Benedict S. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
The significance of protecting cultural and informational resources from damage and loss transcends borders and language. A library disaster plan is important because it provides for guidelines for the prevention and appropriate response to disasters affecting the collections of a given library. It is a working document that needs to be revised and revisited on a regular basis to make changes that fit the needs of the library, the staff and collection. The first and essential step in writing a disaster plan is risk assessment. To assess and identify risks that threaten UST Miguel de Benavides Library collection, this study adopted, and modified Smithsonian National Postal Museum identified Agents of Deterioration and University of California's three types of risks on library collections. Results revealed that collapse of building (due to earthquake) and collapse of shelves (due to overloading) are the biggest risks to library collection. Findings from this study were then used to create the "first" Risk Assessment Report of UST Miguel de Benavides Library for the "current library administration" and risk assessment template is devised for succeeding risk assessment for the library's continual improvement.
Special Problem (Master of Library and Information Science)
Keywords: Risk assessment -- UST Miguel de Bena Vides Library; UST Miguel de Bena Vides Library -- Risk assessment